2021
DOI: 10.3390/cancers13040813
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Auto-Antibodies: Roles, Applications and Open Issues

Abstract: Auto-antibodies are classically associated with autoimmune diseases, where they are an integral part of diagnostic panels. However, recent evidence is accumulating on the presence of auto-antibodies against single or selected panels of auto-antigens in many types of cancer. Auto-antibodies might initially represent an epiphenomenon derived from the inflammatory environment induced by the tumor. However, their effect on tumor evolution can be crucial, as is discussed in this paper. It has been demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 149 publications
1
34
0
Order By: Relevance
“…After surgical resection and chemoradiotherapy for the malignancy, we observed that the ANA of the patient became negative and there was a significant decrease in LA. This reminded us to consider a positive result of ANA and LA in our case dialectically because studies have shown that ANA and LA are associated with malignancy (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 74%
“…After surgical resection and chemoradiotherapy for the malignancy, we observed that the ANA of the patient became negative and there was a significant decrease in LA. This reminded us to consider a positive result of ANA and LA in our case dialectically because studies have shown that ANA and LA are associated with malignancy (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 74%
“…As compared with the traditional tumor markers and the diagnostic targets of the liquid biopsy (e.g., circulating tumor cells, cell-free tumor DNA/RNA, etc.) (reviewed in [ 20 , 21 ]), the TAA-AAbs are characterized by a set of unique properties rendering them particularly suitable for some of the diagnostic applications but significantly limiting their use in others [ 10 , 11 , 12 ].…”
Section: The Basics Of Taas and Taa-aabs In Human Cancermentioning
confidence: 99%
“…Finally, the autoantibodies against bona fide TAAs usually demonstrate very high diagnostic specificity (DSp) in the detection of malignancy (typically 90–95% or higher), whereas their diagnostic sensitivity (DSn) is usually low-to-moderate (typically 10–25% for a single TAA-AAb) [ 12 ]. It implicates the TAA-AAbs as the perfect candidates for the «rule in» tests, whereas their use for «rule out» diagnostics usually requires a combination of TAA-AAbs against several TAAs in a single diagnostic panel, also referred to as autoantibody signature (such as in EarlyCDT ® -Lung test, see Section 3.2 ), concurrent use of TAA-AAbs with other types of biomarkers or diagnostic approaches, or use of the benign tumor-associated TAA-AAbs that disappear upon progression to malignancy and thus may be used for implicit ruling out of malignancy via confident ruling in the benign nature of a tumor (see Section 6 ).…”
Section: The Basics Of Taas and Taa-aabs In Human Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Autoantibodies against nuclear and cytoplasmic autoantigens have been detected in cancer patients, with possible causal mechanisms including autoantigen overexpression from tumour cells and autoantigen release following chemotherapy-induced cell death ( 132 ). Recently, anti-TRIM21 antibodies have been detected in patients with ovarian cancer, the presence of which correlated with better patient survival.…”
Section: Trim21 and Dysregulation Of Cellular Homeostasismentioning
confidence: 99%